Bisexuality in Europe Sexual Citizenship, Romantic Relationships, and Bi+ Identities - Maliepaard, Emiel; Baumgartner, Renate (Global Gender, 2021)
"Bisexuality in Europe offers an accessible and diverse overview of research on bisexuality and bi+ people in Europe, providing a foundation for theorising and empirical work on plurisexual orientations and identities, and the experiences and realities of people who desire more than one sex or gender Counteracting the predominance of work on bisexuality based in Ango-American contexts, this collection of fifteen contributions from both early-career and more senior academics reflects the current state of research in Europe on bisexuality and people who desire more than one sex or gender. The book is structured around three interlinked themes that resonate well with the international research frontiers of bisexual theorising: bisexual citizenship, intimate relationships, and bisexual+ identities. This book is the first of its kind in bringing together research from various European countries including Austria, Finland, Italy, the Netherlands, and Scandinavian countries, as well as from Europe as a wider geographical region.. Topics include pansexual identity, non-monogomies, asylum seekers and youth cultures. This is an essential collection for students, early career researchers, and more senior academics in Gender Studies, LGBTQI Studies and Sexuality Studies. "